Reliability Assessment of Power Generation System With Wind Farm - WANG Xin-wei; ZHANG Jian-hua; JIANG Cheng; YU Lei; SHANG Jingfu (Bulletin of Electrical Engineering and Informatics, 2013)
The reliability of power generation system with wind farm is evaluated based on Monte-Carlosimulation, and in the reliability assessment the randomness of wind speed and power load, failure rate ofwind turbine generator(WTG) and conventional generator are take into account. Monte-Carlo simulationused in power generation system with wind power need large sample size and has low efficiency. So thispaper proposes an improved Monte Carlo method (IMC) based on the combination of Latin HypercubeSampling and Cholesky decomposition, this IMC method is effective to improve sample values coverage ofrandom variables input spaces and the sampling efficiency. The calculation and analysis of improvedIEEE-RTS 79 reliability test systems show that the proposed Assessment algorithm is effective.